The Role of Unwanted Celibacy in Predicting Attitudes Towards Sexual Aggression in Single Men - Aisya, Angelea Putri; Milla, Mirra Noor (Universitas Negeri Malang, 2024)
The emergence of an online community named involuntary celibates (incel), which is widely known for its attitude that condones sexual aggression, is seen as a new threat of violence in Western society. Even though the incel community has not been identified in Indonesia, the shared experience incels have can happen to single men in general. This research aims to test the role of unwanted celibacy in predicting attitudes toward sexual aggression in the Indonesian context, where an incel community is yet to be found. This research uses a quantitative method with 223 single men as participants. The result shows support for the hypothesis that unwanted celibacy does have a role in predicting attitudes toward sexual aggression. Unwanted celibacy is also found to be higher in involuntary single men than in voluntary single men. This research contributes to extending research on unwanted celibacy and involuntary singlehood.